Evolution of plastic transmission strategies in avian malaria. - Stéphane Cornet; Antoine Nicot; Ana Rivero; Sylvain Gandon (PLoS Pathogens, 2014)
Malaria parasites have been shown to adjust their life history traits to changing environmental conditions. Parasite relapses and recrudescences--marked increases in blood parasite numbers following a period when the parasite was either absent or present at very low levels in the blood, respectively--are expected to be part of such adaptive plastic strategies. Here, we first present a theoretical model that analyses the evolution of transmission strategies in fluctuating seasonal environments and we show that relapses may be adaptive if they are concomitant with the presence of mosquitoes in the vicinity of the host. We then experimentally test the hypothesis that Plasmodium parasites can respond to the presence of vectors. For this purpose, we repeatedly exposed birds infected by the avian malaria parasite Plasmodium relictum to the bites of uninfected females of its natural vector, the mosquito Culex pipiens, at three different stages of the infection: acute (∼ 34 days post infection), early chronic (∼ 122 dpi) and late chronic (∼ 291 dpi). We show that: (i) mosquito-exposed birds have significantly higher blood parasitaemia than control unexposed birds during the chronic stages of the infection and that (ii) this translates into significantly higher infection prevalence in the mosquito. Our results demonstrate the ability of Plasmodium relictum to maximize their transmission by adopting plastic life history strategies in response to the availability of insect vectors.